24th Concrete Days 2017 : selected, peer reviewed papers from the 24th International Conference Concrete Days 2017, November 22-23, 2017, Litomyšl, Czech Republic - Nenadálová, Šárka; Johová, Petra; Sajdlova, Tereza (Trans Tech Publications, 2018)
Presented book was collected by results of the 24th International Conference Concrete Days 2017 (Litomyšl, Czech Republic, November 22 - 23, 2017)The papers introduce recent research results in the area of modern concretes and concrete structures, discuss modelling and design of concrete structures, bridges and buildings, properties of concretes as well as significant structural projects and their realizations. Concrete, Reinforced Concrete, Structural Elements, Modeling, Design, Mechanical Properties, Construction Technologies Materials Science.
Keywords: Concrete -- Congresses.; elektronické knihy; electronic books